Benthic hotspots on the northern Bering and Chukchi continental shelf: Spatial variability in production regimes and environmental drivers. (February 2021) - Feng, Zhixuan; Ji, Rubao; Ashjian, Carin; Zhang, Jinlun; Campbell, Robert; Grebmeier, Jacqueline M.
Graphical abstract: Highlights: Key biophysical drivers for 5 benthic hotspots on the Bering/Chukchi shelf are evaluated. Two contrasting spatial regimes and biophysical mechanisms emerge for 5 hotspots. Model results suggest the presence of other hotspots where data are sparse. Model-observation synthesis is useful in studying ice-pelagic-benthic ecosystem. Abstract: Benthic biological hotspots with persistently high macrofaunal biomass exist on the highly advective continental shelf that extends from the northern Bering Sea to the northeast Chukchi Sea. Environmental factors that influence carbon export to the benthos, a key driver for hotspot formation and persistence, remain uncertain. Multiple modeling approaches were used to better understand the combined effects of biological production and physical transport processes on supplying biogenic materials to those biological hotspots. Large data sets of benthic and environmental observations were synthesized, outputs from a pan-arctic ice-ocean-biogeochemical model were analyzed, and particle tracking modeling experiments and statistical analyses were conducted. Two different biophysical mechanisms of biogenic material supply to five benthic hotspot subdomains over a latitudinal range were identified using models and verified using data synthesis. Two hotpots to the south and the north of Bering Strait and the third one in southern Barrow Canyon heavily rely on carbon supplied from upstream biological production. In contrast, the St. Lawrence Island Polynya, southwest of St. Lawrence Island in the northern Bering Sea, and the Northeast Chukchi Sea hotspots are mostly fueled by local production. Spatial statistical modeling of benthic biomass distribution generally recaptured known hotspots but also suggested the likelihood of other probable hotspots in subregions of the biologically productive Gulf of Anadyr and of the topographically controlled Herald Canyon where limited sampling has occurred. The study provides new mechanistic understandings of the oceanographic processes and biophysical interactions that produce organic matter in sea ice and in the water column that subsequently is exported to underlying benthic communities. Combining data synthesis with process-based modeling was critical in understanding the dynamics of these sympagic-pelagic-benthic ecosystems and the potential climate-change-induced ecosystem response in the Pacific Arctic region.